Election Administration and Public Records Responsiveness. (4th May 2022) - Baringer, Anna; Eichermuller, Justin; Zelin, William; Shino, Enrijeta; Smith, Daniel A.
Abstract: Is there an optimum method to elicit public records from election officials? Using a field experiment that randomly assigned the wording and email domains used to solicit public records, we test how county election offices respond to requests under given conditions. We find that the response rates of Florida's 67 Supervisors of Elections (SOE) to a request for election administration data and election protocols after the 2018 General Election varies considerably, but that the formality of the language and the email domain randomly assigned only marginally affects the compliance of election officials to abide by the state's public records statutes. The variance in responses and lack of compliance seems to not be related to who asks for data nor how it is solicited, but rather is idiosyncratic. Despite the largely null findings, our study raises concerns about local election administration and transparency.